Variability in Urine Culture Reporting by Canadian Microbiology Laboratories - Michael A Noble; Shirley Nikiforuk (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the ability of microbiology laboratories to perform and to report urine colony counts.